Expert in My Pocket : A Mobile-Enabled Repository of Learning Resources for the Development of Clinical Skills in Student Health Professionals : Final Report. - Lord, Bill; Oprescu, Florin; Forbes, Helen (Office for Learning and Teaching, 2016)
Mobile communications technology can provide 'just-in-time' support for students in the health disciplines to learn and practice specific clinical skills. This is the final report from a project which created a free, publicly accessible, standardised repository (website) of learning resources comprising video vignettes and supporting materials to enhance student development of psychomotor clinical skills. The training videos are presented from a first person point of view by expert health clinicians who also 'think aloud' as they step through the procedures. The videos are specific to the Australian practice setting and are available in a high-quality format compatible with computers and mobile devices such as smart phones and tablets. A further resource is Quick Response codes for scanning by smart devices to instantly connect the user with the required video.